2013
DOI: 10.1007/s00198-013-2319-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in non-enzymatic glycation and collagen cross-links between human cortical and cancellous bone

Abstract: Purpose Accumulation of collagen crosslinks (advanced glycation end products [AGEs]) produced by non-enzymatic glycation deteriorates bone's mechanical properties and fracture resistance. Although a single AGE, pentosidine, is commonly used as a representative marker, it is unclear whether it quantitatively reflects total fluorescent AGEs in bone. The goal of this study was to establish the relationship between pentosidine and total AGEs in cancellous and cortical bone. Methods Pentosidine and total AGEs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
5
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 28 publications
11
91
5
3
Order By: Relevance
“…Unlike previous reports [5, 43, 44], AGEs did not show a positive relationship with age. This difference can be explained by the presence of larger variations in AGE values and smaller samples in our study compared to previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike previous reports [5, 43, 44], AGEs did not show a positive relationship with age. This difference can be explained by the presence of larger variations in AGE values and smaller samples in our study compared to previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study on in vitro ribosylated cancellous bone showed elevated levels of linear microcracks [10]. Cancellous bone has higher levels of non-enzymatic glycation compared to cortical bone [43] which may influence the level of microdamage accumulation in the bone tissue. The absence of a relationship between AGEs and linear microcrack density in this study may also be due to the limited size of the samples used in the correlation analysis between non-enzymatic glycation and microdamage.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Karim also observed variation in the accumulation of nonenzymatic cross-links between cancellous and cortical bone. (8) Enzymatic cross-links are usually regarded as contributing positively to bone strength; nonenzymatic cross-links, by contrast, are widely held to adversely affect bone material properties. (9) The collagen molecules within each microfibril group coil gradually around each other, with specific kinks that create pockets and potential binding sites for other matrix proteins (5) as well as interactions with cells through integrin-binding (Fig.…”
Section: Normal Bone Tissue; Molecular To Fibrillar Scalementioning
confidence: 99%
“…The effects of AGEs on bone are manifested in two aspects: one is the deleterious modification of bone ultrastructure (e.g., non-enzymatic cross linking in collagen), which may directly lead to the reduced toughness of bone [2,[8][9][10]. The other is the negative modulation of cellular activities in bone remodeling process [2], which include abnormal proliferation, differentiation, and apoptosis of bone cells, such as osteoclasts (OCs), osteoblasts, and osteocytes [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%